Penerapan Algoritma K-Medoids Pada Pengelompokan Penerima Dana Bantuan Sosial Kelurahan Medan Sinembah - Sylvia Situmorang; Rivalri Kristianto Hondro; Sumiati Sumiati (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2022)
Social assistance is generally part of government programs to support minimum sources of income for poor families. To avoid the uneven distribution of social assistance funds provided, it should be noted that the grouping of data on the population of recipients of social assistance funds aims to make the distribution of social assistance funds right on target to people in need and also so that the distribution of social fund assistance is not misused by parties or individuals who are not responsible for the distribution process. Therefore, a technique or method is needed that can be used to help speed up the process of grouping recipients of social assistance funds and get accurate results so that the funds distributed are not misdirected and the technique is commonly referred to as data mining. The K-Medoids algorithm is one of the algorithms that can be used in data mining for clustering or grouping based on certain criteria. For this reason, it is very suitable to use the K-Medoids algorithm for grouping the economic level of the community, where data from each occupation of Medan Sinembah village is used as a criterion.